An exploratory study of information resources used by small manufacturing owners in managing the business in Sedgwick County, Kansas - Hanna, Elaine W. (Kansas State University, 2007)
The purpose of this study was to identify the informational resources used by small manufacturing owners who were in the NAICS 336 sector of manufacturers in Sedgwick County, Kansas, and determine which are most helpful to the owner in managing their business. Prior studies have utilized all small businesses and have not examined industry specific information gathering. A qualitative method was used in the study using a semi-structured interview process to provide in-depth information from the perspective of the small manufacturing owner. The semi-structured interview identified the information resources used by small manufacturing owners in managing their business and the level of helpfulness those resources had for them. Ten small manufacturers whose owner was on site and employed from 20-100 employees were used in the study. Informal resources were most often used by this group of manufacturers. The Internet was identified by the manufacturers as the most important and useful resource to managing their businesses. The small manufacturers used multiple resources to manage their business and rarely relied on only one resource of information whether it was for financial, management, marketing/sales or benchmarking information. Formal sources of information such as colleges, trade schools and seminars were less frequently used. Nonformal resources which were mostly governmental and included the Small Business Association, Small Business Development Center, Manufacturing Extension Partnerships, SCORE, local and federal government resources were rarely used by this group of manufacturers.
Keywords: adult learning; small manufacturing; small business; information resources; Education, Adult and Continuing (0516)